Mechanical, Durability, and Microstructure Investigations on High-Strength Concrete Incorporating Nanosilica, Multi-Walled Carbon Nanotubes, and Steel Fibres - A. Sumathi; D. Elavarasi; B. Karthikeyan; P. Shobana; Senthil Kumaran Selvaraj; Saurabh Dewangan; Baye Molla (Advances in Materials Science and Engineering)
In present research, the strength properties, impact resistance, and durability characteristics of high-strength concrete blended with nanosilica (NS) and reinforced with multi-walled carbon nanotubes (MWCNTs) are discussed. The proportion consists of nanosilica added in a constant addition of 1% and MWCNT added in a varied dosage of 0.025%, 0.05%, 0.1%, 0.15%, and 0.2% by weight of the cement. A total of 11 mixes were made including the control mix having no MWCNT. The other 10 mixes were categorized into two classes with one class having steel fibres incorporated as 1% of the total volume of the concrete along with the other ingredients such as 1% NS and different proportions of MWCNT. The other class was made without steel fibres retaining only the NS and different MWCNT proportions. Besides the standard compression and tension tests, to determine the energy absorbing capacity of the mix specimens, impact test was also performed. The strength tests were carried out for 3, 7, and 28-day curing. Also, durability tests were carried out with sorptivity, porosity, and mass loss of the specimens when exposed to aggressive HCL and H2SO4 acid. To validate the experiment results, microstructure studies such as scanning electron microscopy (SEM) were also conducted on the samples. Among all mixes, 28-day compressive strength (CS) of 0.2% MWCNT with 1% NS and 1% steel fibre mix was found to increase by 22% compared to control concrete.